CHOCOLATE FORMULATION AS DRUG DELIVERY SYSTEM FOR PEDIATRICS - Mayank, Sharma; Kumar, Jain Dinesh (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2012)
Chocolate is highly sophisticated and infinitely a versatile food that can be combined to create completely different taste and texture sensations. The objective of the present study is to develop a palatable chocolate formulation of Domperidone and Cetirizine for pediatric administration and to increase patient’s desire to consume the medication. In present investigation chocolate base is prepared by use of cocoa powder, coco butter, lecithin, and pharmaceutical grade sugar. Thereafter drug is incorporated to prepared chocolate base. The medicated chocolate prepared is evaluated for appearance, moisture content determination using digital Karl Fischer titrator, blooming test, drug content determination & drug excipient interaction by differential scanning calorimetry.Key words: Medicated Chocolate, Pediatrics, Chocolate formulation